Social Enterprises and Their Relationship with Potential Employers: Practices and Logics of Action of the Professional Staff Responsible for Job Placement - Pitteloud, Mélanie (Swiss Journal of Sociocultural Anthropology, 2021)
In our research project, running since October 2019, we study how social enterprises place their participants in the primary labour market. The practices of the social enterprise’s specialists are shaped by the complex relationship between social enterprises, social services that assign their clients to the social enterprises, and the regular labour market, where the enterprises find potential employers for their clients. This paper deals with the relationship between the social enterprises and the regular labour market. In particular, it examines the relationship between the professional staff responsible for job placement and potential employers in the primary labour market.